Engaging African American Faith Leaders as Partners in Ethical Research - Deborah J. Moon; Carol Bailey Nichols; John M. Wallace; Aliya Durham (The University of Alabama, 2024)
This paper outlines an initiative to adapt the Community Partnered Research Ethics Training (CPRET) for the cultural context of the CHURCH (Congregation as Healers Uniting to Restore Community Health) project. The CHURCH project is a community-partnered participatory research project that seeks to promote the mental well-being of African American populations by developing, implementing, and evaluating a mental health training curriculum for faith leaders in Black churches. Participatory research, in which community stakeholders collaborate with researchers as equal partners to address problems impacting marginalized communities, has recently become more popular in academia. Training is necessary to equip community partners with the skills and knowledge required for full research participation. Community partners frequently encounter ethical issues in participatory research, but limited training resources are available to proactively prevent and address such issues. The CPRET was developed through a collaboration between the Clinical and Translational Science Institute and the Human Research Protection Office and Community Research Advisory Board at the University of Pittsburgh. It surveys research processes and core research ethics principles, and it stimulates discussion regarding best practices by engaging participants in scenario-based exercises in which they identify ethical and unethical research. By describing how we utilized the CPRET in the CHURCH project and presenting a summary of participant feedback, we aim to build resources for community-engaged scholars seeking to engage community members in ethical research.